Knowledge engineering and semantic web : 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, proceedings /: 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, proceedings. (2016) - Unknown
No abstract available